Dielectric Modified Separators for High-Voltage and High-Rate Supercapacitors. Issue 12 (1st December 2022) - Bai, Yuge; Li, Nan; Yuan, Boheng; Li, Lei; Yang, Chao; Bin Zhao; Xiao, Bing; Han, Xiaogang
Abstract : Widening the operational voltage window (OVW) of electrolytes has long been attracting researchers' attention as an effective solution for improving the energy density of supercapacitors (SCs). However, the application of commercial cellulose separators in SCs under high voltage is impeded because of the hygroscopic property of hydroxyl functional groups and high self-discharges. Herein, the dielectric materials poly(vinylidene fluoride-co-hexafluoropropylene) PVDF-HFP and TiO2 are employed to modify the surfaces of cellulose separators, which has improved the rate (100% capacitance retention at 20 A g −1 ) and cyclic (over 83% capacitance retention after 10000 cycles) performance of SCs significantly. In addition, the OVW of the organic electrolyte is widened from 2.7 V to 3.8 V. The possible mechanism underlying the function of dielectric materials in SCs is discussed by establishing a model and performing inferential calculation.